From the Black Conciousness movement to the New South Africa : a committed poetry - (:unkn) unknown (My University, 2013)
From 1948 to 1992, the apartheid system in South Africa aimed at systematically denying or even destroying the black population's speech. As a parameter of any oppressive system, the denial of speech was violently and ruthlessly enforced through an institutionalised racist system based on the exploitation of the black population. A resistance movement, therefore, took shape in political movements, unions, and arts, among which literature, and fought for decades to rebuild a black identity, to take part into the writing of history and to establish the foundations of a democratic state. During the 1960s and 1970s, poetry became a considerable force of resistance and struggle, whose aim was to create and sustain the collective will to pull down the structures of oppression. The seizure of speech by poets who recycled the techniques of oral literatures allowed the identification of the crucial relationships between poetics and politics. The Black Consciousness movement was thus structured in and by a poetic speech that appropriated language, words and things through a dialogical process. In spite of major political changes, that dynamics continued during South Africa's political transition, and the poetic voices in contemporary South Africa remain a force that is both disruptive and constructive. It is therefore necessary to define and develop tools for the analysis of the Black Consciousness poetry; the works of Frantz Fanon will prove enlightening in the understanding of a poetry which was a practice and an experiment, fighting for a humanistic perspective based on language.
Keywords: African Research